Perkembangan Kejahatan Internasional dalam Hukum Pidana Internasional: Tinjauan Pertanggungjawaban oleh Peradilan Ad Hoc Internasional - Novianti, Vera; Febriansyah, Artha; Rahayu, Delia; Banjarani, Desia Rakhma; Zulaikha, Almira Novia (Sultan Jurisprudence: Jurnal Riset Ilmu Hukum, 2023)
The number of victims when an international crime occurs does not escape the number of perpetrators who commit crimes, the application or responsibility for this international crime must certainly be considered properly because the perpetrator of this act is not an individual but a country as a subject. Based on this background, the issues raised in this study are: What is behind the establishment of an international court aimed at upholding human rights? How international law is regulated in determining the person responsible for international crimes?. This research is a library research with a normative juridical approach based on applicable legal sources. This research was analyzed descriptively with a qualitative approach. Normative legal research by examining various sources of literature both primary and secondary. The results of this study are the establishment of ad hoc courts, such as the International Military Tribunal (Nuremberg), International Military Tribunal for the Far East (Tokyo), International Criminal Tribunal for former Yugoslavia (ICTY) & International Criminal Tribunal for Rwanda (ICTR) to show that the world already aware of the protection of victims and the need for someone to be responsible. Crimes that occur by deprivation of human rights both on a small and large scale are equally detrimental to victims. Human rights that are upheld regardless of space and time require various countries to work together to protect them. In its responsibilities, the state which is an abstract entity then in its responsibilities will be imposed on individuals who serve as organs of the state.